STUDY OF EMPLOYEE PERFORMANCE: WORKLOAD ON JOB SATISFACTION AND WORK STRESS - I Ketut R. Sudiarditha; Mardi; Leny Margaretha (Jurnal Ilmiah Econosains, 2019)
This study aims to describe the effect of workload on job satisfaction and job stress well on employee performance. Staff from East Jakarta Integrated Services Implementation Unit, 65 respondents were sampled. Data were collected using a questionnaire and analyzed using Structural Equation Modeling (SEM). Hypothesis testing results show positive and insignificant workload on performance, the positive and significant workload on work stress, negative and significant work stress on performance, positive and significant job satisfaction on performance, the positive and significant workload on job satisfaction. This study shows an important influence on research on job satisfaction and job stress; this also shows that job satisfaction and job stress function as intervening variables between workload and employee performance. The findings of this study prove that the workload needs to be indirect to employee performance through job satisfaction and better work pressure. The next researcher can study deeper by using other media and similar objects.